Perapuhan Uranium dengan Metode Hydride–Dehydride: Meningkatkan Efisiensi Bahan Bakar Nuklir dalam Mendukung Transisi Energi - Sakina, Zafira Naja; Ardyanto, Fakhriyan; Supriyadi, Imam; Santoso, Budi (UNIB Press, 2025)
The Hydride–Dehydride (HDH) method is a critical technology in uranium processing, capable of improving the efficiency and quality of nuclear fuel through a more precise embrittlement process compared to conventional techniques. This technology ensures uniform particle size and minimizes material loss during fabrication. This study was conducted using a literature review approach, supported by experimental data obtained during a 2022 internship at the Research Center for Nuclear Fuel Cycle and Radioactive Waste Technology (PRTDBBLNR). The focus of the investigation was the characterization of uranium–molybdenum (U-Mo) alloy before and after the HDH treatment process. The results indicate that heat treatment at 500 Â°C for 5 hours followed by annealing significantly increases the hardness of the U-Mo alloy. A phase transformation was also observed, indicated by the presence of α-U in all post-treatment samples. Nevertheless, the density of the alloy showed no substantial change. The HDH process successfully produced high-purity U-Mo powder at various molybdenum concentration levels. However, increasing Mo content resulted in lower powder density. The morphology of U-7Mo powder exhibited flake-like shapes with a rough surface, which is favorable for further fabrication in advanced fuel element production. Overall, these findings reinforce the relevance and significant potential of HDH technology in supporting advanced nuclear reactor fuel production and strengthening national nuclear energy security in a sustainable manner.The Hydride–Dehydride (HDH) method represents an important innovation in uranium processing to improve the efficiency and quality of nuclear fuel. This technology enables a more precise embrittlement of uranium compared to conventional methods such as milling and crushing, resulting in more uniform particle size and reduced material loss throughout the process. This study adopts a literature-based approach supported by practical work conducted at the Center for Research on Nuclear Fuel Cycle Technology and Radioactive Waste Management (PRTDBBLNR) in 2022, in order to evaluate the effectiveness of HDH in strengthening nuclear energy security in Indonesia. The analysis shows that HDH improves the microstructural quality of uranium and enhances processing yield by minimizing waste generation. These advantages highlight the high relevance of HDH technology in supporting the development of Generation IV nuclear reactors, which emphasize efficiency and sustainability within the fuel cycle. However, its implementation in Indonesia still faces challenges, particularly in terms of industrial infrastructure readiness, safety regulations, and nuclear material protection. Therefore, strategic policies are required to promote further research and technological investment, as well as strong collaboration between academia, government, and industry. Integrating HDH into the national uranium processing roadmap has the potential to establish this technology as a key pillar in ensuring a sustainable nuclear fuel supply and enhancing Indonesia’s energy security in the future.